EKSPLORASI ETNOMATEMATIKA PADA TARIAN GAWI - Stefanus Notan Tupen; Ningsih Ningsih; Sofia Sa'o; Elisabeth Elviana Se’a; Marta Rini Siwo (Program Studi Pendidikan Matematika, 2024)
Culture is something that cannot be avoided in social life because culture is a whole and comprehensive unity that becomes the basis for a relationship between individuals. This unity allows mathematical concepts to be embedded in cultural practices and recognizes that all people develop special ways of facilitating mathematical knowledge. culture-based mathematics learning is part of the way that is perceived to create meaningful and contextualized mathematics learning that is closely related to culture.in ethnomathematics, the relationship between mathematical concepts and culture will be deeply studied. Ethnomathematics is used to explore mathematical values and geometry concepts in gawi traditional dance. The purpose of this study is to describe the concepts of geometry implemented in gawi traditional dance. The concepts of geometry in gawi traditional dance will be reviewed based on the form, dance movements and dancers’ clothing. This study uses descriptive qualitative research with library data collection methods and field data. The data were analyzed descriptively and qualitatively. The results showed that the geometry concepts found in gawi traditional dance were devoted to the material of lines, angles and flat shapes. It was concluded that gawi traditional dance has ethnomathematics concepts, namely circles, parallel lines, acute angles, right angles, obtuse angles, triangles, and rectangles.